Preparation method of nitrogen-doped carbon quantum dot loaded ruthenium-based hydrogen evolution electrocatalyst

By utilizing the conductivity and nitrogen-doped structure of carbon quantum dots in nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalysts, the problem of poor performance of existing catalysts in the entire pH range is solved, and efficient hydrogen electrocatalytic performance in a wide pH range is achieved.

CN119685857AActive Publication Date: 2025-03-25QUZHOU RES INST OF ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411995961.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing hydrogen electrocatalysts perform poorly in a wide pH range (0-14 pH value) and cannot maintain excellent catalytic performance at the full pH range.

Method used

The preparation method of nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst is adopted to synthesize nanoscale, highly dispersed nitrogen-doped carbon quantum dot-supported ruthenium-based catalysts through hydrothermal reactions. The conductivity and nitrogen-doped structure of carbon quantum dots are used to optimize the electron distribution and enhance the electron transfer capability of catalytic active sites.

Benefits of technology

The prepared catalyst exhibits high catalytic activity and stability within the entire pH range, has a low hydrogen evolution overpotential, and can achieve efficient hydrogen evolution reaction at low overvoltage, which is suitable for industrial applications in alkaline seawater environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685857A_ABST
    Figure CN119685857A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water electrolysis hydrogen production catalysts, and particularly relates to a preparation method of a nitrogen-doped carbon quantum dot loaded ruthenium-based hydrogen evolution electrocatalyst, which comprises the following steps: (1) adding alkali lignin and urea into deionized water, uniformly mixing, adding ruthenium trichloride, uniformly mixing, and carrying out hydrothermal reaction to obtain a precursor; and (2) after the precursor is cooled to room temperature, freeze-drying and annealing to prepare the nitrogen-doped carbon quantum dot loaded ruthenium-based hydrogen evolution electrocatalyst. The electrocatalyst prepared by the method provided by the invention has very high catalytic activity and stability, and especially can show excellent catalytic performance in a full pH range (including acidic, neutral and alkaline conditions, namely within 0-14 pH value).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis hydrogen production catalysts, and specifically relates to a method for preparing a nitrogen-doped carbon quantum dot-loaded ruthenium-based hydrogen evolution electrocatalyst. Background Art

[0002] Hydrogen (H 2 ) is considered to be an ideal alternative energy source due to its cleanliness, high efficiency, and abundant reserves. Hydrogen evolution reaction (HER) is a method for obtaining H 2 An effective way to prepare Ru nanoparticles for HER. However, the high cost and limited resources of precious metal Pt-based catalysts limit their widespread application. Therefore, there is an urgent need to develop new catalysts with low cost and high performance. In order to solve the problem of easy agglomeration and deactivation of Ru nanoparticles, the selection of a suitable substrate loading becomes the key to improving their HER performance. Carbon quantum dots show great potential as loading materials, mainly due to their rich surface functional groups and a large number of defects in their structure. These characteristics can effectively disperse Ru nanoparticles and prevent them from agglomerating, thereby improving the stability and activity of the catalyst. In addition, the preparation cost of carbon quantum dots is low, especially the use of alkaline lignin as a carbon source, which not only reduces the synthesis cost, but also provides new possibilities for large-scale applications. The synergistic effect of carbon quantum dots and ruthenium provides a new idea and direction for the design of efficient and inexpensive HER catalysts.

[0003] Lavanya Korampattu and others (Lavanya Korampattu, Sidharth Barik, AjmalPandikassala, Rajashri R. Urkude, Sreekumar Kurungot, Paresh L. Dhepe. Chemistry of Materials , 2024, 36, 4262) A ruthenium-based catalyst (Ru-CCP) was synthesized by nitrogen-doping carbon materials using chitosan as a source of nitrogen and carbon. Nitrogen doping plays a key role in improving the catalytic performance of carbon materials because it can generate defects and active sites and enhance the interaction between ruthenium and carbon materials. The Ru-CCP catalyst prepared by a single-step pyrolysis process exhibits excellent electrocatalytic performance for HER in alkaline media. 25 mA cm-2 was achieved at an overpotential as low as 46 mV. -2The current density of Ru-CCP exceeds that of commercial Pt / C catalyst under the same conditions. In addition, the high catalytic performance of Ru-CCP is due to the unique interaction between ruthenium and surface nitrogen groups (especially pyridinic and pyrrolic nitrogen). Nitrogen doping significantly modulates the electronic environment of ruthenium nanoparticles, thereby improving the catalytic activity. This catalyst not only exhibits excellent hydrogen evolution activity, but also proves the potential of sustainable materials (such as chitosan) in clean H 2 Potential in production.

[0004] Liu et al (Liu, L., Liu, N., Dai, C., Xu, R., Yu, G., Wang, N., & Chen, B. Catalysis Today , 2024, 436, 114751) synthesized a MoS-based 2 Ruthenium nanoparticle catalysts (5Ru@MoS 2-1.4 ), and by regulating MoS 2 The structural characteristics and ruthenium loading of MoS2+ enhanced the electrocatalytic performance of HER. Specifically, MoS2+ with different sulfur vacancy contents was synthesized using CO2 gas as a structure-directing agent. 2 Support, among which MoS 2-1.4 The ruthenium nanoparticles (average particle size of 2 nm) were uniformly loaded on the MoS by wet impregnation. 2-1.4 superior.

[0005] The presence of ruthenium nanoparticles and MoS 2 -1.4 The sulfur vacancies in the support act synergistically, effectively improving the hydrogen evolution activity and showing a low overpotential (55 mV @10 mA cm-2 ) and a smaller Tafel slope (68.6 mV dec -1 ). The catalyst has excellent catalytic performance in alkaline media and is 2 Based on HER catalyst, it shows significant advantages. In addition, sulfur vacancies not only promote the dispersion of ruthenium nanoparticles, but also inhibit the agglomeration of particles, further improving the reaction efficiency. This study provides a method to improve MoS by optimizing the synergistic effect of the carrier and ruthenium. 2 A new strategy to improve the performance of hydrogen evolution catalysts effectively solves the problems of ruthenium catalyst particle agglomeration and insufficient carrier activity.

[0006] Although the above-mentioned catalysts are active in alkaline environments, they cannot maintain activity under a wide pH range, that is, they cannot have excellent catalytic performance over the entire pH range. Therefore, it is very important to research and develop a nitrogen-doped carbon quantum dot-supported ruthenium-based catalyst that has excellent catalytic performance over the entire pH range to fill the gap in the existing technology. Summary of the invention

[0007] The present invention aims to solve the above technical problems and provides a method for preparing a nitrogen-doped carbon quantum dot-loaded ruthenium-based hydrogen evolution electrocatalyst. The electrocatalyst prepared by the method has high catalytic activity and stability, and in particular can exhibit excellent catalytic performance in the entire pH range (including acidic, neutral and alkaline conditions, i.e., within the pH range of 0-14).

[0008] The technical solution of the present invention is: A method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst comprises the following steps: (1) adding alkaline lignin and urea into deionized water and mixing them evenly, then adding ruthenium trichloride and mixing them evenly, and performing a hydrothermal reaction to obtain a precursor; (2) After the precursor is cooled to room temperature, freeze-dried and annealed to prepare a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst. The structure of the catalyst is: nano-sized and highly dispersed nitrogen-doped carbon quantum dots as a supporting material, a ruthenium-based catalyst supported by nitrogen-doped carbon quantum dots, the carbon quantum dots forming a carbon-based material with good electrical conductivity, the ruthenium species combined with the carbon quantum dot matrix through strong interaction, the nitrogen-doped structure helps to optimize the electron distribution and enhance the electron transfer ability of the catalytic active site. The raw materials act synergistically under the method of the present invention, thereby improving the hydrogen evolution reaction activity of the catalyst.

[0009] The crystal structure, morphology and electronic structure of the catalyst will affect its hydrogen evolution performance at different pH values, and the nitrogen doping amount has a direct effect on the active sites of the catalyst. The increased nitrogen source can provide more active sites, but too high a nitrogen doping amount may also lead to excessive concentration or uneven distribution of active sites, thereby affecting the stability and activity of the catalyst at different pH values. In addition, carbon quantum dots are used as carrier materials, and their surface functional groups such as -COOH, -C-O and -C-N can undergo adsorption reactions with water molecules, which is beneficial to the cracking reaction of water molecules, thereby promoting the electrocatalytic hydrogen evolution reaction. In a certain catalyst structure, too many carbon quantum dots will reduce the dispersion of ruthenium nanoparticles in the carbon quantum dots. , which changes the overall structural stability of the catalyst and reduces the active sites of the catalyst, reduces the catalytic activity, and causes the catalyst to undergo structural changes or collapse during the reaction. Too few carbon quantum dots and insufficient carriers to disperse and stabilize the ruthenium nanoparticles will also reduce the active sites of the catalyst, thereby reducing the catalytic activity. It will also lead to imperfect construction of the conductive network, affecting the transmission rate of electrons in the catalyst, and will also affect the structure of the catalyst, causing the catalyst to be destroyed or worn during the reaction and deactivated. Therefore, the addition ratio of alkali lignin, urea, and ruthenium trichloride must be strictly controlled to prepare a catalyst with high catalytic activity and stability and that can exhibit excellent catalytic performance over the entire pH range. In order to prepare the catalyst of the present invention, in step (1) of the present invention, the mass ratio of the alkali lignin, urea, and ruthenium trichloride is preferably 6:8:1.

[0010] In the system of the present invention, in order to ensure that the ruthenium nanoparticles can be evenly dispersed and prevent the catalyst particles from agglomerating, preferably, the solid-liquid ratio of the total mass of the alkali lignin, urea, and ruthenium trichloride to deionized water in the present invention is 70-80:1 mg / ml. If the solid-liquid ratio is too large, it may cause the catalyst particles to agglomerate, reducing the dispersibility of the catalyst and the number of active sites. If the solid-liquid ratio is too low, the catalyst particles may not be fully formed or grown, which will also affect the dispersibility and catalytic performance of the catalyst system.

[0011] In the method of the present invention, the hydrothermal reaction time and temperature have a significant effect on the structure, morphology, crystallinity and catalytic performance of the catalyst. In order to obtain the catalyst of the present invention, preferably, in step (1) of the present invention, the hydrothermal reaction conditions are: keeping the reaction at 100-200°C for 7.5-8.5 h.

[0012] In order to ensure the structural integrity of the reaction product, obtain a catalyst with high catalytic activity and stability, especially a catalyst that can exhibit excellent catalytic performance in the entire pH range (including acidic, neutral and alkaline conditions, i.e., within the pH value of 0-14), preferably, in step (2) of the present invention, freeze drying is performed for 46-50 hours. If the freeze drying time is less than 46 hours, the water in the catalyst is not completely sublimated, and the residual moisture will affect the activity of the catalyst. If the drying time is more than 50 hours, it will cause changes in the catalyst structure, resulting in the destruction of the active sites. Therefore, in order to ensure the performance of the catalyst, the freeze drying time needs to be controlled.

[0013] In order to promote structural transformation and the formation of active sites and ensure the catalytic activity and stability of the catalyst, it is very important to control the annealing conditions. Preferably, in step (2) of the present invention, the specific annealing steps are: in an argon atmosphere, at 5-10°C min -1 The heating rate is raised to 500-900°C, and then kept warm for 2-2.5h. In the catalyst of the present invention, the heating rate is controlled within the scope of the present invention to ensure the activity and stability of the catalyst. If the heating rate is too high, it will cause uneven crystal growth, increase or concentration of internal stress, affect the formation of microporous structure and reduce mechanical strength, and also cause aggregation or coverage of active sites, reduce exposure of active sites, and if the heating rate is too low, it will also cause uneven crystal growth, excessive development of microporous structure, and allow the catalyst to be in a high temperature state for a long time, thereby affecting the long-term stability of the catalyst; during annealing, the holding time is too long, the crystal growth is too large, the specific surface area will be reduced, and the catalytic activity will be affected. The holding time is too short, the catalyst active components cannot be fully formed or dispersed, thereby affecting the activity of the catalyst, and the crystals fail to grow uniformly, which will also affect the catalyst specific surface area and the number of active sites. Therefore, in order to obtain the catalyst of the present invention, it is necessary to strictly control the conditions of degradation.

[0014] The present invention also provides the use of the catalyst prepared by the method for preparing the nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst in the electrolysis of water to produce hydrogen. Preferably, the water is alkaline seawater or water with a pH value in the range of 0-14, that is, the catalyst of the present invention can exhibit excellent catalytic performance in a wide pH range (including acidic, neutral and alkaline conditions), is particularly suitable for alkaline seawater environments, can exhibit high catalytic activity in alkaline seawater electrolysis, and is suitable for industrial applications in actual seawater electrolysis to produce hydrogen.

[0015] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The electrocatalyst prepared by the method of the present invention has high catalytic activity and stability, and in particular can exhibit excellent catalytic performance in a wide pH range (including acidic, neutral and alkaline conditions, i.e., within a pH value of 0-14), has a low hydrogen evolution overpotential, can achieve efficient hydrogen evolution reaction under low overvoltage, and exhibits good current density.

[0016] 2. The electrocatalyst prepared by the method of the present invention is particularly suitable for alkaline seawater environment and can exhibit high catalytic activity in alkaline seawater electrolysis. Chloride ions and other impurities under alkaline conditions have little effect on the catalyst. The catalyst of the present invention still maintains a highly efficient hydrogen evolution reaction in such a complex environment and is suitable for industrial applications in actual seawater electrolysis to produce hydrogen.

[0017] 3. The method of the present invention has simple and efficient process steps. The ruthenium-based catalyst loaded with nitrogen-doped carbon quantum dots can be prepared by a one-step hydrothermal method. By strictly controlling the addition ratio of alkaline lignin, urea, and ruthenium trichloride, as well as strictly controlling the hydrothermal conditions, the synthesis of the catalyst can be achieved in a one-step hydrothermal reaction, which greatly simplifies the preparation process, reduces intermediate steps and energy consumption, and has good industrial application prospects.

[0018] 4. The present invention uses alkali lignin as a carbon source, which is a renewable resource with a wide range of sources and low cost. It avoids the problems of high cost and environmental pollution in the preparation of traditional carbon sources, has the characteristics of cleanliness, environmental protection and sustainability, and has strong economic benefits.

[0019] 5. The method of the present invention only requires strict control of the addition ratio of alkaline lignin, urea, and ruthenium trichloride and the hydrothermal reaction conditions. No other raw materials need to be added. The hydrothermal reaction can be completed in one step to prepare the catalyst of the present invention which has high catalytic activity and stability and can exhibit excellent catalytic performance in the full pH range.

[0020] 6. The preparation method of the present invention is clean, environmentally friendly, pollution-free and sustainable. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a transmission electron microscope (TEM) image of the catalyst prepared in Example 1.

[0022] Figure 2 Polarization curves of the electrochemical test of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and 20 wt % Pt / C in 1 M KOH solution.

[0023] Figure 3 Polarization curves of the electrochemical test of the catalysts prepared in Example 1 and Comparative Examples 1-3 in 1 M PBS solution.

[0024] Figure 4The catalysts prepared in Example 1 and Comparative Examples 1-3 were heated to 0.5 MH 2 S0 4 Polarization curves of electrochemical tests of solutions.

[0025] Figure 5 Polarization curves of the electrochemical test of the catalysts prepared in Example 1 and Comparative Examples 1-3 in alkaline seawater solution.

[0026] Figure 6 Polarization curves of the electrochemical test of the catalysts prepared in Example 1, Comparative Example 4 and 20 wt % Pt / C in 1 M KOH solution.

[0027] Figure 7 Polarization curves of the electrochemical test of the catalysts prepared in Example 1, Comparative Example 5, Comparative Example 6 and 20 wt % Pt / C in 1 M KOH solution. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0029] A method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst, comprising the following steps: (1) Alkali lignin and urea were dissolved in 10 mL of deionized water to obtain a uniform mixed solution, and then ruthenium trichloride was added to the solution, stirred for 30 min until it was completely dispersed, and then transferred to a 50 mL reactor, sealed, and subjected to hydrothermal reaction at 150° C. for 8 h to obtain a precursor; the mass ratio of the alkali lignin, urea, and ruthenium trichloride was 6:8:1; the total added mass of the alkali lignin, urea, and ruthenium trichloride was 75 mg; (2) After the reaction is completed, the reactor is cooled naturally to room temperature, the product is taken out and freeze-dried for 48 hours to obtain a dried product; (3) The dried product was placed in a tube furnace under an argon atmosphere at 5 °C min -1 The temperature was raised to 500°C and kept at this temperature for 2.5 hours. After cooling to room temperature, the product was ground into a uniform powder to obtain a black powder, which is a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst, hereinafter referred to as Ru / NC. The transmission electron microscope TEM image of the catalyst is shown in FIG. Figure 1 As shown, from Figure 1It can be seen that the ruthenium nanoparticles are well supported by the carbon quantum dots, and the lattice fringes of the ruthenium (101) crystal plane and the graphite carbon (100) wafers of the carbon quantum dots as carriers can be clearly seen. The small-sized crystalline nanoparticles have a relatively high density of catalytic active sites, and the Ru nanoparticles are uniformly supported on the carbon quantum dots with a highly uniform size distribution. Example 2

[0030] A method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst, comprising the following steps: (1) Alkali lignin and urea were dissolved in 10 mL of deionized water to obtain a uniform mixed solution, and then ruthenium trichloride was added to the solution, stirred for 30 min until it was completely dispersed, and then transferred to a 50 mL reactor, sealed, and subjected to a hydrothermal reaction at 100° C. for 8.5 h to obtain a precursor; the mass ratio of the alkali lignin, urea, and ruthenium trichloride was 6:8:1; and the total added mass of the alkali lignin, urea, and ruthenium trichloride was 80 mg; (2) After the reaction is completed, the reactor is cooled naturally to room temperature, the product is taken out and freeze-dried for 50 hours to obtain a dried product; (3) The dried product was placed in a tube furnace under an argon atmosphere at 8°C min -1 The temperature was raised to 700° C., kept at this temperature for 2.5 h, and after cooling to room temperature, the product was ground into a uniform powder to obtain a black powder, which is the nitrogen-doped carbon quantum dot-loaded ruthenium-based hydrogen evolution electrocatalyst. Example 3

[0031] A method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst, comprising the following steps: (1) Alkali lignin and urea were dissolved in 10 mL of deionized water to obtain a uniform mixed solution, and then ruthenium trichloride was added to the solution, stirred for 30 min until it was completely dispersed, and then transferred to a 50 mL reactor, sealed, and subjected to hydrothermal reaction at 200° C. for 7.5 h to obtain a precursor; the mass ratio of the alkali lignin, urea, and ruthenium trichloride was 6:8:1; and the total mass of the alkali lignin, urea, and ruthenium trichloride was 70 mg; (2) After the reaction is completed, the reactor is cooled naturally to room temperature, the product is taken out and freeze-dried for 46 hours to obtain a dried product; (3) The dried product was placed in a tube furnace under an argon atmosphere at 10 °C min -1 The temperature was raised to 900°C and kept at this temperature for 2 h. After cooling to room temperature, the product was ground into a uniform powder to obtain a black powder, which is the nitrogen-doped carbon quantum dots-loaded ruthenium-based hydrogen evolution electrocatalyst.

[0032] Comparative Example 1 The difference from Example 1 is that no alkali lignin and urea are added, that is, the amount of alkali lignin and urea added in step 1) is 0 mg, and the rest is the same as Example 1, and the obtained catalyst is recorded as Ru NPs.

[0033] Comparative Example 2 The difference from Example 1 is that no ruthenium source is added, that is, the amount of ruthenium trichloride added in step 1) is 0 mg, and the rest is the same as Example 1. The obtained catalyst is recorded as CDs.

[0034] Comparative Example 3 The difference from Example 1 is that this comparative example directly uses hydrophilic carbon paper without adding a catalyst, that is, the hydrophilic carbon paper is directly tested without adding an electrode material, which is recorded as CP.

[0035] Comparative Example 4 The difference from Example 1 is that the mass ratio of the alkali lignin, urea and ruthenium trichloride is 3:4:1, and the rest is the same as Example 1.

[0036] Comparative Example 5 The difference from Example 1 is that the hydrothermal reaction is carried out at 150° C. for 10 h, and the rest is the same as Example 1.

[0037] Comparative Example 6 The difference from Example 1 is that the hydrothermal reaction is carried out at 150° C. for 6 h, and the rest is the same as Example 1.

[0038] The catalyst prepared by Example 1, Comparative Example 1, Comparative Example 2 and 20 wt% Pt / C was loaded onto the hydrophilic carbon paper as the electrode material, and the corresponding catalyst loading was 1 mg / cm 2 The electrocatalytic hydrogen evolution performance was tested using a three-electrode system. Figure 2 .

[0039] like Figure 2 As shown in Figure 2, Ru / NC exhibits excellent hydrogen evolution activity in 1 M KOH, achieving 10 mA cm -2 The current density of CDs only requires an overpotential of 32 mV, which is significantly lower than the 49 mV and 117 mV of 20 wt% Pt / C and Ru NPs, indicating that Ru / NC has considerable prospects in industrial applications. The current density of CDs at an overpotential of 293 mV is only 3.16 mA cm -2 , indicating that the active sites are not located on the carbon quantum dots.

[0040] The catalyst prepared in Example 1 and Comparative Examples 1-3 is loaded onto the hydrophilic carbon paper as the electrode material, and the corresponding catalyst loading is 1 mg / cm 2 The electrocatalytic hydrogen evolution performance was tested using a three-electrode system. Figure 3-5shown.

[0041] like Figure 3 As shown in Figure 2, Ru / NC also has good catalytic performance in a neutral environment of 1 M PBS, reaching 10 mA cm -2 The current density of CDs only needs a low overpotential of 38 mV, which is lower than the 121 mV of Ru NPs. Meanwhile, in a neutral environment, the current density of CDs at an overpotential of 336 mV is only 1.02 mA cm -2 The current density of 2.5 Å indicates that it also does not serve as an active site.

[0042] like Figure 4 As shown, in an acidic environment 0.5 MH 2 S0 4 Hydrogen evolution performance in solution, up to 10 mA cm -2 At a current density of 1.34 W, Ru / NC only requires a low overpotential of 47 mV, while Ru NPs require a low overpotential of 79 mV. The overpotential of Ru / NC is significantly lower than that of RuNPs, indicating that Ru / NC maintains a high catalytic activity.

[0043] like Figure 5 As shown in the figure, the hydrogen evolution performance was tested in an alkaline seawater environment, and the current density reached 10 mA cm -2 When the overpotential of Ru / NC is 35 mV, the overpotential of Ru NPs is 45 mV, and the overpotential of CDs is 152 mV. Ru / NC is significantly lower than Ru NPs and CDs, indicating that the Ru / NC of the present invention exhibits excellent catalytic activity in alkaline seawater.

[0044] The catalyst prepared in Example 1, Comparative Example 4 and 20 wt% Pt / C was loaded onto the hydrophilic carbon paper as the electrode material, and the corresponding catalyst loading was 1 mg / cm 2 The electrocatalytic hydrogen evolution performance was tested using a three-electrode system. Figure 6 shown.

[0045] like Figure 6 As shown, the 6:8:1 used in Example 1 showed excellent hydrogen evolution activity in 1 M KOH, obtaining 10 mA cm -2 The current density only requires an overpotential of 32 mV, which is significantly lower than the 90 mV and 49 mV of 20wt% Pt / C with 3:4:1 and Pt / C, proving that the ratio of 6:8:1 is the optimal ratio.

[0046] The catalyst prepared by Example 1, Comparative Example 5, Comparative Example 6 and 20 wt% Pt / C was loaded onto the hydrophilic carbon paper as the electrode material, and the corresponding catalyst loading was 1 mg / cm 2The electrocatalytic hydrogen evolution performance was tested using a three-electrode system. Figure 7 shown.

[0047] like Figure 7 As shown, the 8h hydrothermal catalyst in Example 1, denoted as Ru / NC-8 in this figure, exhibited excellent hydrogen evolution activity in 1 M KOH, obtaining 10 mA cm -2 The current density only requires an overpotential of 32 mV, which is significantly lower than 49mV, 48mV and 45mV of 20wt% Pt / C, 6h annealing in Comparative Example 6 (Ru / NC-6) and Comparative Example 5 (Ru / NC-8), proving that the selected 8h is the optimal hydrothermal time.

[0048] In summary, the nitrogen-doped carbon quantum dots supported ruthenium-based hydrogen evolution electrocatalyst prepared by the synergistic effect of the various steps in the method of the present invention exhibits excellent HER activity in the entire pH range (including acidic, neutral and alkaline conditions, i.e., within the pH value of 0-14) and in alkaline seawater, thereby significantly expanding its applicability.

[0049] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst, characterized in that: The following steps are involved: (1) adding alkali lignin and urea into deionized water and mixing them evenly, then adding ruthenium trichloride and mixing them evenly, and performing a hydrothermal reaction to obtain a precursor; (2) After the precursor cools to room temperature, freeze-drying and annealing are performed to prepare a nitrogen-doped carbon quantum dot-loaded ruthenium-based hydrogen evolution electrocatalyst; In the step (1), the mass ratio of the alkali lignin, urea and ruthenium trichloride is 6:8:

1.

2. The method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst according to claim 1, characterized in that: The material-liquid ratio of the total mass of the alkali lignin, urea, and ruthenium trichloride to deionized water is 70-80:1 mg / ml.

3. The method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst according to claim 1, characterized in that: In the step (1), the hydrothermal reaction conditions are: keeping the temperature at 100-200° C. for 7.5-8.5 h.

4. The method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst according to claim 1, characterized in that: In the step (2), freeze drying is performed for 46-50 hours.

5. The method for preparing a nitrogen-doped carbon quantum dot-supported ruthenium-based hydrogen evolution electrocatalyst according to claim 1, characterized in that: In step (2), the specific annealing steps are: in an argon atmosphere, at 5-10°C min -1 The temperature is raised to 500-900°C at a heating rate and then kept at this temperature for 2-2.5h.

6. Use of the catalyst prepared by the method according to any one of claims 1 to 5 in hydrogen production by electrolysis of water.

7. The use according to claim 6, characterized in that; The water is alkaline seawater or water with a pH value in the range of 0-14.

Citation Information

Patent Citations

  • Carbon quantum dot membrane / Ru nanometer crystal for hydrogen production through water electrolysis as well as preparation method thereof

    CN109136968A

  • Preparation method of nitrogen-doped carbon-based ruthenium-loaded catalyst for hydrogen evolution by electrolysis

    CN113684502A